2005
DOI: 10.1080/10412905.2005.9698897
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Rose Water Volatiles

Abstract: A volatile concentrate obtained from rose water (ex. Rosa damascena fl owers) by liquid-liquid extraction with dichloromethane was studied by GC and GC/MS. The volatiles consisted mainly of 2-phenylethanol (69.7-81.6%), linalool (1.5-3.3%), citronellol (1.8-7.2%), nerol (0.2-4.2%), geraniol (0.9-7.0%) along with rose oxides and all other characteristic minor rose compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 6 publications
3
34
0
1
Order By: Relevance
“…The major compounds in the samples analyzed in this work, i.e., linalool and α-terpineol in orange blossom hydrosols, 2-phenylethanol, citronellol and geraniol in both rose sp. hydrosols, were also in high amounts in hydrosols analyzed in previous studies, and variations in 6-methyl-5-hepten-2-one, linalool, α-terpineol, citronellol, geraniol, and 2-phenyl ethanol amounts among samples for example were also previously reported (Agarwal et al, 2005;Aslam Khan & Shoaib Ur, 2005;Jeannot et al, 2005;Mahboubifar, Shahabipour, & Javidnia, 2014;Ulusoy et al, 2009; Albert Vieille SAS unpublished data) ( Table 2). The major compounds contained in the EO phase of rose and orange blossom hydrosols are known for their antimicrobial properties.…”
Section: Resultssupporting
confidence: 73%
“…The major compounds in the samples analyzed in this work, i.e., linalool and α-terpineol in orange blossom hydrosols, 2-phenylethanol, citronellol and geraniol in both rose sp. hydrosols, were also in high amounts in hydrosols analyzed in previous studies, and variations in 6-methyl-5-hepten-2-one, linalool, α-terpineol, citronellol, geraniol, and 2-phenyl ethanol amounts among samples for example were also previously reported (Agarwal et al, 2005;Aslam Khan & Shoaib Ur, 2005;Jeannot et al, 2005;Mahboubifar, Shahabipour, & Javidnia, 2014;Ulusoy et al, 2009; Albert Vieille SAS unpublished data) ( Table 2). The major compounds contained in the EO phase of rose and orange blossom hydrosols are known for their antimicrobial properties.…”
Section: Resultssupporting
confidence: 73%
“…It was noted that percentages of phenylethyl alcohol in rose water volatiles investigated were comparable to those from Indian [3,[10][11] , Iranian [12] and Turkish [13][14] rose waters. Rose water is valued for high levels of phenylethyl alcohol, which is responsible for the characteristic aroma of fresh rose flowers [10][11][12] . In contrast, the percentages of phenylethyl alcohol in rose oils were much lower (< 1.6%, Table 1).…”
Section: Chemical Profiles Of Rose Water and Oilmentioning
confidence: 68%
“…Numerous studies have been carried out on chemical composition of rose oil [2][3][4][5][6][7][8][9] and water [3,[10][11][12][13][14] from different countries. Literature survey revealed that there is no chemical investigation on rose water volatiles of R. damascena and R. rugosa from Southeast China.…”
Section: Rosa Damascenamentioning
confidence: 99%
“…By using the latter technique (SWE), two years earlier,Özel and Clifford [6] reported that the essential oil of R. canina was mainly dominated by 2-phenethyl alcohol and benzyl alcohol. Volatile oil samples of R. damascena from India [21], France [22], and Iran [13] extracted by using liquidliquid extraction of the aromatic water, head-space, and hydrodistillation methods showed an aromatic profiles dominated by alcohols mainly 2-phenylethyl alcohol, citronellol, nerol, and geraniol, respectively. Another report from India reported that the essential oil obtained by the distillation of fresh flowers of R. damascena was dominated by alcohols (55.25-83.41%) with 2-phenethyl alcohol being the main constituent [18].…”
Section: Chemical Composition Of the Aromatic Water Frommentioning
confidence: 99%